Structural Health Monitoring 2019 2019
DOI: 10.12783/shm2019/32137
|View full text |Cite
|
Sign up to set email alerts
|

Field Assessment of Ambient Vibration-Based Bridge Scour Detection

Abstract: Scour is the main cause of bridge failure in the United States and around the world. It involves the loss of soil from around bridge foundations due to fast flowing water. Monitoring bridge scour is challenging as it occurs underwater. A scour monitoring technique that uses accelerometers on the bridge piers and deck to provide real-time measurements of ambient vibration, from which scour-induced changes in the natural frequencies of the bridge may be monitored, has recently emerged. However, field validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The use of natural frequency to detect bridge pier integrity has been reported in Japanese railway bridges [19], although it has not been widely adopted in other parts of the world. A recent field deployment of this technique on a reinforced concrete road bridge indicated that the measurement error in natural frequency derived using ambient vibration data can be high, compared to the expected sensitivity of natural frequency changes due to scour [20][21][22]; therefore, it is important to experimentally establish the natural frequency sensitivity to scour of different bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural frequency to detect bridge pier integrity has been reported in Japanese railway bridges [19], although it has not been widely adopted in other parts of the world. A recent field deployment of this technique on a reinforced concrete road bridge indicated that the measurement error in natural frequency derived using ambient vibration data can be high, compared to the expected sensitivity of natural frequency changes due to scour [20][21][22]; therefore, it is important to experimentally establish the natural frequency sensitivity to scour of different bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The FDD method is based on the SVD of the measured PSD matrix of the recorded response, ( ), at discrete frequencies of = 1 , 2 , … , , as shown in Equation 5, where ( ) is a matrix of singular vectors and ( ) is a diagonal matrix of singular values. Over the frequency range associated with each peak in the first singular values, the structural response is dominated by a single vibration mode, with the first singular vector being an estimate of the mode shape and the corresponding first singular value being the auto-PSD of the modal contribution [52].…”
Section: Background On Fdd and Data Analysis Proceduresmentioning
confidence: 99%